Impact of information technology industries on urban form: a case study of Indiranagar in Bangalore. (16th October 2012) - Gowda, Krishne; Filho, Walter Leal; Shobha, M.N.; Sridhara, M.V.
The purpose of this paper is to highlight the impact of rapid growth of IT Industry on Indiranagar, Bangalore, as a case study. An appraisal of this development has to be made as otherwise it will lead to further irreparable damage to the region as a result of this developmental process. The study shows that the area is developing haphazardly resulting in tremendous pressure on the existing infrastructure and environmental degradation in residential areas. This has led to the recognition of the need for planned IT parks. The implications of this study are significant for the authorities concerned, while formulating policies.